Noninvasive prenatal diagnosis of cobalamin C (cblC) deficiency through target region sequencing of cell‐free DNA in maternal plasma. (26th December 2019) - Han, Lianshu; Chen, Chao; Guo, Fengyu; Ye, Jun; Peng, Zhiyu; Qiu, Wenjuan; Wang, Yaoshen; Li, Wei; Zhang, Huiwen; Liang, Lili; Wang, Yu; Wang, Huanhuan; et al.
Abstract: Objective: This study aimed to validate the feasibility of haplotype‐based noninvasive prenatal diagnosis (NIPD) of cobalamin C (cblC) deficiency. Method: This method includes three steps: First, targeted sequencing was performed on 21 families affected by cblC deficiency (including the couples and probands). Second, parental haplotypes linked with the pathogenic variant were determined using the genotypes of trios. Then, the fetal haplotypes were inferred through a parental haplotype assisted hidden Markov model (HMM). The NIPD results were confirmed by using the invasive procedures. Results: Twenty‐one fetal genotypes were successfully inferred by NIPD including three compound heterozygotes with cblC deficiency, nine heterozygote carriers of cblC deficiency, and nine normal fetuses. The NIPD results were confirmed using the invasive procedures with 100% concordant rate. Conclusion: This result has shown that haplotype‐based NIPD of cblC deficiency has high concordant rate and indicated potential clinical utility as a pregnancy diagnosis method for high‐risk carrier couples. Abstract : What's already known on this topic? Genetic analyses and biochemical analyses are used for the prenatal diagnosis of methylmalonic acidemia (MMA). Noninvasive prenatal diagnosis (NIPD) of isolated MMA has been reported in only one case using digital PCR. What this study adds? Design and validation of haplotype‐based NIPD of cblC deficiency in a relatively large patient cohort using target region sequencing. A novel fetal fraction (FF) calculation method is introduced using single nucleotide polymorphisms (SNPs) and it can accurately determine FF.